The Plant Negative-Sense RNA Virosphere: Virus Discovery Through New Eyes - Bejerman, Nicolás; Debat, Humberto; Dietzgen, Ralf G. (Frontiers in Microbiology, 2020)
While the use of high-throughput sequencing (HTS) for virus diagnostics has been extensively investigated, the importance of this technology as a valuable tool for discovery of novel viruses has received less attention. In this review, we consider the application of HTS approaches to uncover novel plant viruses with a focus on the negative-sense, single-stranded RNA virosphere. Plant viruses with negative-sense and ambisense RNA (NSR) genomes belong to several taxonomic families, including Rhabdoviridae, Aspiviridae, Fimoviridae, Tospoviridae and Phenuiviridae. They include both emergent pathogens that infect a wide range of plant species, and potential endophytes which appear not to induce any visible symptoms. As a consequence of biased sampling based on a narrow focus on crops with disease symptoms, the number of NSR plant viruses identified so far represents only a negligible fraction of this type of viruses present in the virosphere. Detection and molecular characterization of NSR viruses has often been challenging, but the widespread implementation of HTS has facilitated not only the identification but also the characterization of the genomic sequences of at least 70 NSR plant viruses in the last seven years. Moreover, continuing advances in HTS technologies and bioinformatic pipelines, concomitant with a significant cost reduction has led to its use as a routinely method of choice, supporting the foundations of a diverse array of novel applications such as quarantine analysis of traded plant materials and genetic resources, virus detection in insect vectors, analysis of virus communities in individual plants, and assessment of virus evolution through ecogenomics, among others. The insights from these advancements are shedding new light on the extensive diversity of NSR plant viruses and their complex evolution, and provide an essential framework for improved taxonomical classification of plant NSR viruses as part of the realm Riboviria. Thus, HTS-based methods for virus discovery, our ‘new eyes’, are unraveling in real time the richness and magnitude of the plant RNA virosphere.